2021
DOI: 10.1016/j.ciresp.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Top 100. Revisión de los artículos más citados sobre cirugía laparoscópica del páncreas

Abstract: c i r e s p . 2 0 2 0 ; x x ( x x ) : x x x -x x x informació n del artículo Historia del artículo:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…With the development of the COVID-19 pandemic, some authors have published their surgical experience during the pandemic [6,10,11] or have reported their protocol to treat surgical patients with COVID-19 [12][13][14][15][16][17][18]. Nevertheless, as far as we know, the reduction of ACSA observed during this pandemic has never been properly reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of the COVID-19 pandemic, some authors have published their surgical experience during the pandemic [6,10,11] or have reported their protocol to treat surgical patients with COVID-19 [12][13][14][15][16][17][18]. Nevertheless, as far as we know, the reduction of ACSA observed during this pandemic has never been properly reported.…”
Section: Discussionmentioning
confidence: 99%
“…Medical and nursing staff were redistributed and outpatient clinic visits were cancelled or conducted online or by phone [3,4]. Departments of Surgery were, for sure, affected by these changes; elective procedures were delayed, staff members were allocated to reinforce the ICU and surgeons were reorganized in closed working https://doi.org/10.1016/j.ijsu.2020.07.002 Received 19 May 2020; Received in revised form 29 June 2020; Accepted 3 July 2020 groups to avoid infections between them [5,6]. Certainly, another one of these changes was a reduction in Acute Care Surgery Activity (ACSA).…”
Section: Introductionmentioning
confidence: 99%